Corporate culture's influence on creative teams - Ziębicka, Kaja (Creativity in Business Practice. Part 2, 2019)
The subject of the chapter covers the issues of organizational culture, teamwork and creativity. The theoretical part of the work, based on literary sources, aimed at defining the elements and types of organizational culture as well as the characteristics of teams capable of generating creative ideas and developing innovative solutions. The practical part of the work was based on the results of the survey conducted using the questionnaire method, in which the employees of a selected recruitment company took part. The study aimed to determine the characteristics of organizational culture of the company under study, the practices used in the organization and, moreover, the opinion of a group of surveyed employees on the functioning of project teams created in various business lines of the organization.